2022
DOI: 10.3389/fnagi.2022.787552
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Decline Is More Accurate When Metamemory Is Better

Abstract: ObjectiveSubjective cognitive decline (SCD) has emerged as one of the first manifestations of Alzheimer’s disease (AD). However, discrepancies in its relationship with tests of memory and other cognitive abilities have hindered SCD’s diagnostic utility. Inter-individual heterogeneity in metamemory, or memory awareness, and the use of clinical measures of cognition lacking sensitivity to early cognitive dysfunction, may contribute to these discrepancies. We aimed to assess if the relationship between SCD and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…In a very recently published study, it was also found that the accuracy of an individual's metamemory can influence to which degree SCD is associated with measures of semantic proactive interference. 31 The frequency of patients with impaired awareness was equivalent in the aMCI and the mild dementia groups and only approximately 25% of the patients had impaired awareness. This is a low number compared to the findings of a previous study in which more than 60% of MCI and mild dementia patients had impaired insight.…”
Section: Discussionmentioning
confidence: 91%
“…In a very recently published study, it was also found that the accuracy of an individual's metamemory can influence to which degree SCD is associated with measures of semantic proactive interference. 31 The frequency of patients with impaired awareness was equivalent in the aMCI and the mild dementia groups and only approximately 25% of the patients had impaired awareness. This is a low number compared to the findings of a previous study in which more than 60% of MCI and mild dementia patients had impaired insight.…”
Section: Discussionmentioning
confidence: 91%
“…Increasingly, studies are revealing the utility of SCD for detecting important imaging and cognitive markers of preclinical AD 3–8,13. However, subjective perceptions of cognitive decline are not always indicative of pathologic cognitive aging,36 and it is important to identify the factors that may contribute to SCD more broadly 37. This is important because it informs the circumstances under which SCD is most likely to be a marker of emerging AD, and because it allows for the identification of potentially modifiable factors that can improve perceptions of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8]13 However, subjective perceptions of cognitive decline are not always indicative of pathologic cognitive aging, 36 and it is important to identify the factors that may contribute to SCD more broadly. 37 This is important because it informs the circumstances under which SCD is most likely to be a marker of emerging AD, and because it allows for the identification of potentially modifiable factors that can improve perceptions of cognitive decline. Historically, while much emphasis has been placed on mood as a primary contributor to SCD, [38][39][40][41] it is increasingly appreciated that both SCD and mood may together herald emerging AD.…”
Section: Discussionmentioning
confidence: 99%
“…Zvýšené seba-monitorovanie typické pre ľudí s PP podporuje patologickú interpretáciu benígnych omylov (Teodoro, Edwards & Isaacs, 2018;Larner, 2021), nemožno však ani vylúčiť fakt, že podporuje aj schopnosť hypervigilantného človeka všimnúť si aj mierne zmeny skôr, než ich je možné objektívne zachytiť. V tejto súvislosti môže určitá úroveň PP byť v súlade s lepšou metapamäťou, ktorá zlepšuje presnosť, s akou je pociťovaný SCD prediktabilný vo vzťahu k vývinu objektívneho poklesu kognície (Chapman et al, 2022). Ďalší výskum by sa mal zamerať na to, ako odlíšiť, do akej miery môže PP prispieť k skorej identifikácii kognitívnych zlyhaní, a do akej miery ide o patologizáciu stavu.…”
Section: Tabuľka 6 Korelácie Subjektívnych Sťažností Na Kogníciu a Ne...unclassified